Perancangan dan Pemanfaatan Website untuk Mendukung Promosi Desa Wisata Apar Pariaman - Putri Anggraini; Sularno Sularno; Dio Prima Mulya; Renita Astri; faradika faradika; Zulfahmi Zulfahmi (LPPM Universitas Dharma Andalas, 2022)
The problem faced by Miftahul Huda Islamic Unggul Terpadu Elementary School teachers is that they are less competent in marketing schools so they are lacking, they still market door to door or manually so they are less effective and efficient. The problem faced by the teacher prompted the service team to assist in assisting the school's digital marketing training as a means to improve the program to increase new student admissions. From the problems mentioned above, of course, the right solution must be found to overcome them by referring to several theories and related research findings regarding improving teacher competence, especially in increasing digital marketing soft skills. Therefore, this service activity will try to provide solutions faced by partners by holding training and continuing by forming discussion forums